PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN MODEL PADANG TAHUN PELAJARAN 2013/2014 - Zawardi, Andra; Haryono, Yulia; Lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACTThe background of this research is the students donât do participation in discussion and still low comprehend mathematic concept.The purpose of this research is to find out students comprehension by using Numbered Head Together in learning cooperative with quiz is better than conventional learning at grade eighth at MTsN Model Padang. This is an experimental research.Technigue of random sampling eighthfour grade class was selected as the experimental and control classes of eighthfive grade.The instrument that is used Quiz and essay form. The hypothesis test is U Mann-whitney test is obtained Zhitung = -2,6616 is less than Ztabel = -1,65. The hypothesis is accepted. In conclusion, students comprehension by using Numbered Head Together in cooperative learning with Quiz is better than conventional learning at grade eighth at MTsN Model Padang.